Noção de pessoa e configurações de parentesco entre artistas Drag Queens da cidade de Fortaleza/CE - Portela, Antonio Plácido Matos (2021)
The present dissertation aims to investigate the kinship configurations among drag queen artists from the city of Fortaleza. This research tries to understand the parental system played by people who practice the montação and, even though they don’t share a blood bond, they build a type o family based on alliances. This research also uses as an exemplary case the life journey of my main interlocutor, Ketlen Williams Negra d’Ryelloon. The chapters of this dissertation are structured as follows: 1) birth processes and a drag queen personhood; 2) adoption processes and the role of mothers in the development of their daughters, which I also argue about the nomination system and the building of relatives through an aesthetics continuity; and 3) processes of self-affirmation and the search for independece. The metodology of this reasearch is based on deep interviews, a few ethnographic experiences in the places where performances are accomplished and comparison of images that come from the social media of my main interlocutor, especifically Facebook and Instagram.